University Staff's Work Motivation: Do Personal Factors Make A Difference? - Duong, Minh-Quang; Le, Thi-Thu-Yen (Thai Journal of East Asian Studies, 2019)
This study explores perceptions of university staff toward work motivation, as well as the relationship between perceived personal factor and staff’s work motivation. Questionnaires measuring factors of work motivation were distributed to 71 full-time working staffs of the Vietnam National University Ho Chi Minh City. The empirical results reveal that the levels of work motivation of staff in VNU-HCM are moderately high. The findings of this study also indicated that there were significant differences in work motivation levels in terms of age, length of employment, academic qualification, and income per month.